Destination Satisfaction and Revisit Intention of Tourists: Does the Quality of Airport Services Matter?. (January 2020) - Seetanah, Boopen; Teeroovengadum, Viraiyan; Nunkoo, Robin
This study focuses on the link between tourists' satisfaction with the quality of airport services at a destination and their intention to revisit. The influence of tourists' overall satisfaction with a destination on their behavioral intentions has been well established both at theoretical and empirical levels; however, the particular role of satisfaction with airport services has been so far largely neglected. Researchers have recognized the vital importance of tourists' experience with airport services because of the fact that the airport is the first and last encounter that they experience when visiting a country. As such, the focus of the present study pertains to evaluating the satisfaction level of tourists visiting Mauritius and examining its resulting effect on their behavioral intentions. The study uses the survey methodology for data collection and involved the distribution of self-administered questionnaires to a sample of 1, 721 tourists at the SSR airport in Mauritius. Exploratory factor analysis is used to extract meaningful dimensions of airport services and a multinomial probit analysis is conducted to test for the impact of satisfaction with airport services on revisit intention while taking into account other control variables. Interestingly, airport services are seen to significantly influence the probability of repeat tourism.